Arsenic Levels in Drinking Water and Urinary Biomarkers: Implications for Public Health and Nutrition in Poboya Village, Central Sulawesi, Indonesia - Nahrun, Muh Mulyadi (Journal of Global Nutrition, 2025)
Arsenic contamination from artisanal gold mining poses significant public health and nutritional risks. This cross-sectional study assessed arsenic levels in drinking water and urinary biomarkers among 100 residents of Poboya Village, Central Sulawesi. Eight drinking water sources were tested, and all showed arsenic concentrations far above the permissible limit (>10 µg/L), ranging from 40–70 µg/L. Elevated urinary arsenic levels (≥35 µg/L) were found in 75% of participants. Duration of residence was significantly associated with urinary arsenic concentration (p = 0.026), while occupation, nutritional status, and distance from pollutant sources showed no significant associations. These findings indicate widespread arsenic exposure through contaminated drinking water, underscoring the need for improved water safety and integrated public health and nutrition interventions in the community.